Circular economy and inclusion as effective tools to prevent ecological threats in rural areas during military operations - V.G. Shcherbak; Y.I. Danko; S. Tereshchenko; O. Nifatova; N. Dehtiar; O. Stepanova; V. Yatsenko (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: In the context of war, rural areas of Ukraine have encountered serious environmental challenges that threaten not only the environment but also the resilience of communities. This study aims to examine the impact of circular economy and inclusion on reducing the risk of ecological threaten, addressing resource usage issues, and restoring ecology in rural areas during wartime. The objectives include analyzing the potential of the circular economy and inclusive practices to solve the mentioned problems.METHODS: Various methods were used to analyze the impact of circular economy and inclusion on the environmental situation in rural areas. The foundation of the research was based on reviewing scientific literature and analyzing previous studies, which allowed for assessing the potential impact of these factors on the environment. The main methods applied included quantitative data analysis through regression modeling, which helped identify the relationship between the level of inclusion and circular economy practices with changes in the level of ecological threaten. Additionally, the use of taxonomy allowed determining the level of ecological threaten, while cluster analysis was used to distribute territories based on the level of ecological threaten ecocide. Factor analysis helped to understand how circular economy measures and inclusion affect ecological threaten, and regression analysis was used to confirm the validity of the research hypotheses.FINDINGS: The study demonstrates integrating circular economy principles with active community engagement significantly mitigates ecological threats in wartime rural Ukraine, achieving a 45 percent risk reduction. Direct positive impact of circular economy practices and inclusivity on environmental health, marking a 30 percent ecological improvement, was discovered. Research highlights innovations and inclusive practices enhance biodiversity by 25 percent and boost agricultural productivity by 20 percent. These findings underline the urgent need for a shift towards a sustainable management model combining circular economy principles with extensive social inclusion, essential for ecological resilience and rejuvenation of rural Ukrainian areas amidst conflict.CONCLUSION: Implementing circular economy and inclusivity in rural Ukraine reduces ecological threats by 45 percent, enhancing biodiversity and agricultural productivity. Circular economy and inclusion are key strategies for ensuring ecological resilience and restoration in rural areas of Ukraine during war time. The implementation of circular economy, waste reduction, resource reuse, development of low-carbon technologies, and active community engagement in environmental initiatives can contribute to the resilience and recovery of affected regions.